Importance of bone marrow examination in cases of pancytopenia: A morphological study in a tertiary care center (Asian Journal of Medical Sciences, 2024)
Background: Anemia, leukopenia, and thrombocytopenia are all combined as pancytopenia. It could be a symptom of many diseases that directly or indirectly impact the bone marrow. The cause of pancytopenia, however, differs depending on the location. An essential step in determining the cause of pancytopenia is bone marrow aspiration (BMA).Aims and Objectives: This study aimed to determine the causes of pancytopenia and the morphology of the bone marrow in pancytopenia patients.Materials and Methods: This study was carried out over a year in the pathology department of a tertiary care facility in central India. Patients taking chemotherapy or radiation therapy were excluded from the study. Inclusion Criteria: Cases with hemoglobin